Karakteristik fisikokimia dan organoleptik teh kombucha sarang semut (Myr-mecodia sp.) pada variasi konsentrasi gula dan lama fermentasi - Br Barus, Peronika; Sarungallo, Zita; Meilan Lisangan, Meike (Program Pascasarjana Universitas Papua, 2026)
ABSTRACT: Sarang semut (Myrmecodia sp.) has potential to be developed as a raw material for functional beverages through fermentation processes; however, the effects of sugar formulation and fermentation time on its product characteristics have not been extensively studied. This study aimed to analyze the effects of sugar concentration and fermentation time on the physicochemical and organoleptic characteristics of sarang semut kombucha tea as a basis for the development of functional beverage products. The research was conducted using an experimental method with a factorial Completely Randomized Design (CRD), consisting of two factors: sugar concentration (20, 25, and 30%) and fermentation time (0, 4, 6, 8, 10, 12, and 14 days). The results showed that sugar concentration and fermentation time significantly affected the physicochemical characteristics of sarang semut kombucha tea. The pH value decreased during fermentation, from 4.15-4.23 on day 0 to 2.64-2.76 on day 14. Total soluble solids (TSS) increased with increasing sugar concentration and fermentation time, ranging from 14.5-17.0 °Brix at 20% sugar concentration, 18.0-19.9 °Brix at 25%, and 21.7-23.8 °Brix at 30%. Total acidity also increased with fermentation time, from 7.71-8.10% on day 4 to 15.63-17.37% on day 14. Meanwhile, organoleptic test results indicated that sugar concentration and fermentation time did not significantly affect color, aroma, taste, or the intensity of aroma and taste, with ratings ranging from neutral to slightly liked. The resulting sarang semut kombucha tea exhibited a brownish-yellow color, a moderately strong characteristic ant nest aroma, and a moderately sour taste intensity.